Marketing Mix Strategy to Increase Sales of Atlantis Store's Mobile Phone Business, Jempong Baru, Mataram - Fina Rohmatika; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The purpose of this research is to determine how the contribution of the marketing mix can increase sales and to understand how effective the marketing mix is in adding sales value at the Atlantis mobile company. The results of this study reveal that the contribution of the marketing mix to the Atlantis mobile business includes the main products, which are mobile phones and their accessories, where prices vary depending on the type of product chosen, and the business location is very strategic as it is located in the city center. The promotion of a business is carried out by implementing appealing strategies that utilize promotional tools such as sales promotion activities and the design and location of outdoor advertisements. Additionally, there are two categories of advertising used, namely individual sales and mass sales. Employees of the business provide good and friendly service, and the execution of processes is in accordance with the systems and procedures established by the company. The tangible evidence of this business can be seen from the buildings and facilities present. Regarding the effectiveness of the marketing mix, advertising plays the most significant role in increasing sales. This research employs a literature study method with a descriptive-qualitative approach, which includes the analysis of various scientific sources, articles, and journals relevant to the marketing mix.